2022
DOI: 10.31080/asds.2022.06.1411
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the Internal and External Surfaces of Zirconia Restorations; between Past and Present Trends. A Review of Literature

Abstract: Objectives:The optimum zirconia bonding protocol have been always a mystery to be solved throughout the past years. The purpose of this review is to go through the innumerable surface treatment methods and protocols concerned with the both internal and external zirconia surface treatment.Study selection, Data and Sources: An electronic Pubmed, Medline and Google scholar search was done to attain In-vitro studies on zirconia surface treatments published in english, with time frame between 2013 and 2020.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To form a chemical bond with silane, Z-prime is used to create a chemical link with zirconia because it includes 10-MDP phosphate ester monomer, which chemically binds with the oxide layer of zirconia and increases bond strength. (El-Ashkar and Nabil 2022) Other published research, however, has shown that the use of a laser does not improve the adhesion of composite resins and zirconia.…”
Section: Discussionmentioning
confidence: 97%
“…To form a chemical bond with silane, Z-prime is used to create a chemical link with zirconia because it includes 10-MDP phosphate ester monomer, which chemically binds with the oxide layer of zirconia and increases bond strength. (El-Ashkar and Nabil 2022) Other published research, however, has shown that the use of a laser does not improve the adhesion of composite resins and zirconia.…”
Section: Discussionmentioning
confidence: 97%
“…This increase may also be attributed to the hydroxylation on the surface, and the acid solutions might have contributed to the micromechanical retention by increasing the micro-roughness of the zirconia (30). The objective of the hydroxylation was to enhance the bond strength between zirconia and the resin cements by increasing the concentration of OHgroups on the zirconia surface (18,19). Nevertheless, these applications may not be suitable for clinical use mainly because they contain hazardous acids that might be toxic (18).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the hydroxylation was to enhance the bond strength between zirconia and the resin cements by increasing the concentration of OHgroups on the zirconia surface (18,19). Nevertheless, these applications may not be suitable for clinical use mainly because they contain hazardous acids that might be toxic (18). They may be suitable only for laboratory usage with proper safety protocols, including adequate ventilation and personal protective equipment (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations